1995
DOI: 10.1001/archsurg.1995.01430080094015
|View full text |Cite
|
Sign up to set email alerts
|

Familial Nonmedullary Thyroid Cancer

Abstract: Familial nonmedullary thyroid carcinoma has a high incidence of multifocality and invasion and a high rate of local recurrence. Aggressive initial treatment and careful follow-up seem to be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(74 citation statements)
references
References 30 publications
4
67
3
Order By: Relevance
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The low prevalence of FNMTC, together with small sampling series and short follow-up studies, has limited consistent information on patient survival as well. Some studies have reported distinct clinical behaviours (3,16,17,18,19,20,21), but others have claimed that there are no differences between the two entities (1,22,23,24,25). Our present data seem to support the latter view, as we did not observe, overall, statistical differences in clinicopathological features, DNA ploidy status and outcome measures between familial PTC (whole series) and sporadic PTC.…”
Section: Discussionsupporting
confidence: 72%
“…However, two findings may suggest the opposite in our study: the significantly higher presence of tumour multifocality in the subgroup of familial PTC with index cases and the trend to higher occurrence of extrathyroidal extension in the subgroup of familial PTC with three or more affected elements, where accurate diagnosis is more easily demonstrated. It is well known about the association of these adverse pathological characteristics with disease aggressiveness, the former often being documented in familial PTC (16,19,20). The same holds true to the higher incidence of vascular invasion and bilateral tumour growth found in this group, as compared with sporadic PTC, although without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There is increasing evidence that there is a familial component to PTC, with between 3.5-6.2% of PTC patients having one or more first degree relatives with thyroid carcinoma (2)(3)(4)(5)(6). Familial aggregations have been noted (7)(8)(9) and we reported the first recognised families predisposed to an autosomal dominant form of PTC with associated multinodular goitre (MNG) (10) (Fig. 1).…”
Section: Introductionmentioning
confidence: 64%
“…(Grossman et al 1995, Loh 1997, Alsanea et al 2000, Uchino et al 2002, Lee et al 2014. However, others have reported no increase in disease aggressiveness compared with sporadic thyroid cancer (Loh 1997, Ito et al 2009, Robenshtok et al 2010, Pinto et al 2014.…”
Section: Introductionmentioning
confidence: 99%